Comparison of Two Antiretroviral Therapy Regimens in Human Immunodeficiency Virus (HIV−) Infected Pregnant Women. (4th October 2017) - Tate, Danielle; Samson, Fernand; Christiansen, Mary; Meyers, Lindsay; Cashion, Kitty; Wang, Jenny; Cruz, Marina Santa; Gomez, Luis
Abstract: Background: Combined antiretroviral therapy (cART) in human immunodeficiency virus (HIV)-infected pregnant women reduces the maternal-to-child transmission (MTCT) rate from a baseline of 25% to less than 2% when the HIV viral load (VL) is <1, 000 copies/mL. The traditional cART is composed of 2 nucleoside reverse transcriptase inhibitor (NRTI-) and 1 protease inhibitor (PI)-class drugs. There is limited information on the effects of VL reduction in pregnancy with alternative cART modalities containing either an integrase strand transfer inhibitor (INSTI) or a non-NRTI (nNRTI). Objective: We sought to compare the HIV VL near delivery in HIV-infected pregnant women receiving 2 NRTI plus 1 PI (traditional cART) to those receiving 2 NRTI plus 1 INSTI or 1 nNRTI (alternative cART). Methods: Prospective cohort study of pregnant HIV-infected women from 2010 through 2016 receiving care in our high-risk obstetric infectious disease clinic. Women were included if they had at least 2 VL (before and after intervention) obtained during pregnancy. Our primary outcome was the rate of VL <1, 000 copies/mL near delivery. Results: We collected data in 274 subjects (traditional cART=156, alternative cART=118). After adjusting for confounders, the rate of VL <1, 000 copies/mL near delivery was comparable among women receiving the traditional treatment (121/156, 77.6%) to the alternative cART (101/118, 85.6%); P = 0.2765, RR 1.474 (0.733–2.967). More women in the alternative cART group (66.9%) had undetectable VL near delivery compared with the traditional cART group (46.1%); P = 0.0103, RR 2.002, 95% CI 1.178–3.403. There were 5 cases (1.8%) of MTCT: 1 in the traditional cART group and 4 in 1 in the alternative cART group. Conclusion: After adjusting for confounders, our cohort of women receiving either traditional or alternative cART regimens achieved similar rate of HIV VL <1, 000 copies/mL near delivery. Further studies are needed to replicate our findings. Disclosures: All authors: No reported disclosures.